Implementation of a Surgical Safety Checklist: Impact on Surgical Team Perspectives - Papaconstantinou, Harry T. (the Academic Division of Ochsner Clinic Foundation, 2013)
BACKGROUND: The World Health Organization (WHO) surgical safety checklist has been shown to decrease mortality and complications and has been adopted worldwide. However, system flaws and human errors persist. Identifying provider perspectives of patient safety initiatives may identify strategies for improvement. The purpose of this study was to determine provider perspectives of surgical safety checklist implementation in an effort to improve initiatives that enhance surgical patients' safety. METHODS: In September 2010, a WHO-adapted surgical safety checklist was implemented at our institution. Surgical teams were invited to complete a checklist-focused questionnaire 1 month before and 1 year after implementation. Baseline and follow-up results were compared. RESULTS: A total of 437 surgical care providers responded to the survey: 45% of providers responded at baseline and 64% of providers responded at follow-up. Of the total respondents, 153 (35%) were nurses, 104 (24%) were anesthesia providers, and 180 (41%) were surgeons. Overall, we found an improvement in the awareness of patient safety and quality of care, with significant improvements in the perception of the value of and participation in the time-out process, in surgical team communication, and in the establishment and clarity of patient care needs. Some discordance was noted between surgeons and other surgical team members, indicating that barriers in communication still exist. Overall, approximately 65% of respondents perceived that the checklist improved patient safety and patient care; however, we found a strong negative perception of operating room efficiency. CONCLUSION: Implementation of a surgical safety checklist improves perceptions of surgical safety. Barriers to implementation exist, but staff feedback may be used to enhance the sustainability and success of patient safety initiatives.